2014
DOI: 10.1071/rd13133
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational programming of fetal nephron deficits and sex-specific adult hypertension in rats

Abstract: A developmental insult that restricts growth in the first generation has the potential to program disease in subsequent generations. The aim of this study was to ascertain transgenerational growth and cardio-renal effects, via the maternal line, in a rat model of utero-placental insufficiency. Bilateral uterine vessel ligation or sham surgery (offspring termed first generation; F1 Restricted and Control, respectively) was performed in WKY rats. F1 Restricted and Control females were mated with normal males to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 49 publications
7
47
2
Order By: Relevance
“…Although F1 growth-restricted male offspring have increased blood pressure as previously published (7,12,18), our model of growth restriction does not program obesity (17,44). Previous studies have demonstrated that F0 paternal obesity adversely affects embryo development and function, which can lead to the development of F1 cardiovascular and metabolic dysfunction (19,20,24).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although F1 growth-restricted male offspring have increased blood pressure as previously published (7,12,18), our model of growth restriction does not program obesity (17,44). Previous studies have demonstrated that F0 paternal obesity adversely affects embryo development and function, which can lead to the development of F1 cardiovascular and metabolic dysfunction (19,20,24).…”
Section: Discussionmentioning
confidence: 50%
“…Although both F1 male and female offspring have organ deficits, only F1 male rats develop hypertension and metabolic dysfunction in the absence of obesity (7,(9)(10)(11)(12). We, and others, have also demonstrated that these deficits are not limited to F1 offspring and can be transmitted, by mothers born small, to the second generation (13)(14)(15)(16)(17)(18). The second-generation (F2) transgenerational effects transmitted via the F1 paternal line after growth restriction are less well characterized.…”
Section: Introductionmentioning
confidence: 88%
“…2009; Gallo et al. 2012a, 2013). Urinary measurements of sodium, chloride, potassium (Rapidchem 744, Bayer Healthcare, CA), glucose, creatinine, albumin, and total protein (Cobas Integra 400; Roche Diagnostics, Burgess Hill, UK) were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Female offspring which were not hypertensive had normal mesenteric, renal, and femoral artery stiffness but had uterine artery endothelial dysfunction and increased wall stiffness [109••]. Utero-placental insufficiency has been shown to decrease nephron number and cyclooxygenase-2 (COX-2) in a rat model [110] and to increase umbilical and carotid artery stiffness in sheep dams due to disrupted extracellular matrix deposition [111]. Increased markers of renal apoptosis and decreased urinary sodium excretion [112] were also noted in rats and newborn piglets.…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%